Metagenomic Analysis of Biocide-Treated Neotropical Oil Reservoir Water Unveils Microdiversity of Thermophile Tepidiphilus - Bedoya, Katherine; Niño, Jhorman; Acero, Julia; Jaimes-Prada, Ronald; Cabarcas, Felipe; Alzate, Juan F. (Frontiers in Microbiology, 2021)
Microorganisms are capable of colonizing extreme environments like deep biosphere and oil reservoirs. The prokaryotes diversity in exploited oil reservoirs is composed of indigenous microbial communities and artificially introduced microbes. In the present work, high throughput sequencing techniques were applied to analyze the microbial community from the injected and produced water in a neotropical hyper-thermophile oil reservoir located in the Orinoquia region of Colombia, South America. Tepidiphilus is the dominant bacteria found in both injection and produced waters. The produced water has a higher microbial richness and exhibits a Tepidiphilus microdiversity. The reservoir injected water is recycled and treated with the biocides glutaraldehyde and tetrakis-hydroxymethyl-phosphonium sulfate (THPS) to reduce microbial load. This process reduces microbial richness and selects a single Tepidiphilus genome (T. sp. UDEAICP_D1) as the dominant isolate. Thermus and Hydrogenobacter were subdominants in both water systems. Phylogenomic analysis of the injection water dominant Tepidiphilus positioned it as an independent branch outside T. succinatimandens and T. thermophilus lineage. Comparative analysis of the Tepidiphilus genomes revealed several genes that might be related to the biocide-resistant phenotype and the tolerance to the stress conditions imposed inside the oil well, like RND efflux pumps and type II toxin-antitoxin systems. Comparing the abundance of Tepidiphilus protein-coding genes in both water systems shows that the biocide selected Tepidiphilus sp. UDEAICP_D1 genome has enriched genes annotated as ABC-2 type transporter, ABC transporter, Methionine biosynthesis protein MetW, Glycosyltransferases, and two-component system NarL.